Activation of subnational platform to broker institutional changes - CGIAR Research Program on Climate Change, Agriculture and Food Security (2017)
The platform is an effective intermediary that channel development and climate change activities. the platform members are very active and connected to different initiatives by building on the capacity established. For instance, the three platforms established in the Upper West region are used for other climate projects (ASSAR project).